(untitled) (West African Journal on Sustainable Development, 2024)
It is unarguable that the rural area carries about 70% of the country’s untapped natural resources and the bulk of her landmass, however rural communities are still subsisting under poor conditions devoid of opportunities and options, emerging from decades of callous neglect of Rural Infrastructure Investment in rural areas. Available records show that Rural Infrastructure is disproportionately low or even non-existent in many rural areas of Nigeria and several efforts at improving the records have not achieved the desired results. Two major approaches to Infrastructure investment are; self-help among rural dwellers and external assistance as offered by planners and implementers of policies to this effect. This paper addresses the second approach focusing on attainment of SDG goal 11. Area specific Rural Infrastructure provisions are canvassed for to boost the rate of impact by capitalizing on the people’s participatory approach which entrenches the sustainable development indicators. Recommendations made include a call on governments to pursue Rural Infrastructure provision as an impetus for achieving the SDG goal of making our communities safe, resilient and sustainable.